Assessing the determining factors of corporate social and environmental responsibility reporting in Bangladesh: moderating effect of industry sector and country of origin - Khatun, Kazi Masuma (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis, 2018)
First of all, this research has been conducted with an attempt to examine the motivation for CSER practices and thus reporting of both local and global organization residing in Bangladesh. CSER and CSER reporting seems to have been exploited in Bangladesh, with limited constructed legislation and instruction for the companies. Consequently, the study strongly believes that the research on CSER reporting provides the broader view of the current situation of CSER practices in Bangladesh.